2001
DOI: 10.1111/0002-9092.00179
|View full text |Cite
|
Sign up to set email alerts
|

The Extent, Pattern, and Degree of Market Integration: A Multivariate Approach for the Brazilian Rice Market

Abstract: The extent, pattern, and degree of integration are analyzed in a multivariate system with cointegrating restrictions. The extent of the market is found by identifying locations that are linked by trade and where prices share identical long-run information (permanent component). The pattern of integration characterizes interdependence and is analyzed by estimating a vector error correction model. The degree of integration is calculated with persistence profiles of the long run relations. We demonstrate that biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 20 publications
1
47
0
6
Order By: Relevance
“…However, there are (n 2 -n)/2 possible pairs. Hence, all but n-1 pairs will be redundant (Asche, Bremnes and Wessells, 1999;Gonzalez-Rivera and Helfand, 2001). A potential problem is therefore that one might obtain different conclusions depending on which pairs one chooses in applied work, although this is theoretically impossible.…”
mentioning
confidence: 99%
“…However, there are (n 2 -n)/2 possible pairs. Hence, all but n-1 pairs will be redundant (Asche, Bremnes and Wessells, 1999;Gonzalez-Rivera and Helfand, 2001). A potential problem is therefore that one might obtain different conclusions depending on which pairs one chooses in applied work, although this is theoretically impossible.…”
mentioning
confidence: 99%
“…There is a possibility of accidental correlation 19 , although this is also interpreted as evidence of inter-market transactions. Second, in many practical analyses, models to measure the degree of market integration often require strong assumptions concerning transaction costs 2,4,16,18 . The EG test and ECM in this paper also assume a linear relationship between prices in integrated markets.…”
Section: Discussionmentioning
confidence: 99%
“…Transactions surrounding 22 UB (9,12,13,14,17,18,19,22), Z China (2,5,7,14,16,19,20), Z Russia (1,3,4,8,11,17,19,21), Z Mt Khangai (1, 2, 3, 4, 5, 7), Z Forest (8,11,13,17) and Z UB (22).…”
Section: Spatial Characteristics Of Market Integrationmentioning
confidence: 99%
“…As can be seen from table 4 above the null of 4, 3 and 2 common 16 Testes are done for each lag but it is presented at 15 th cumulative lag. Since each lag is independent and have chi2 distribution their sum or their cumulative value will also have chi2 distribution 17 It is observed that in these case most of the information criterions were picking the same lag. So it could be possible that the performance of the information criterions is dependent on white noisiness of the data.…”
Section: Cointegration Analysis To Search For Markets Under Rule Of Omentioning
confidence: 95%
“…First the highest probability of serial correlation observed in any cumulative lag from 1 to 15 th . In case the statistics is significant additional statistics is given in cumulative lag selected by information criterions 17 . And for these markets the highest serial correlation is observed at 9 th cumulative lag but still it is not significant even at 15% and there is no need for second statistics.…”
Section: Cointegration Analysis To Search For Markets Under Rule Of Omentioning
confidence: 99%